Prenatal diagnosis of megaduodenum using ultrasound: a case report - Kaihui Zeng; Dongmei Li; Yao Zhang; Chengcheng Cao; Ruobing Bai; Zeyu Yang; Lizhu Chen (BMC, 2021)
Abstract Background Congenital megaduodenum is a rare disorder; however, its prenatal diagnosis has not been reported previously. We report the case of an abdominal cystic mass in a fetus that was later diagnosed as megaduodenum. Case presentation An abdominal cystic mass was found during ultrasonography of a fetus at 11 weeks of gestation. The mass progressively enlarged with gestation. The amniotic fluid volume decreased and then returned to normal. During the last prenatal ultrasound examination, the mass was observed communicating with the stomach; therefore, duodenal dilation was suspected. Finally, the patient was diagnosed with megaduodenum caused by a developmental defect in the nerve plexus. Conclusions Congenital megaduodenum is a differential diagnosis of massive fetal abdominal cystic masses. Ultrasound examinations of such masses communicating with the stomach may help determine the diagnosis.